IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA - Muhammad Rafli Aditya Rahman; I Dewa Putu Juwana; Ni Komang Wirasti (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Motivation to learn plays a crucial role in achieving learning success in school. Low motivation to learn among students results in low learning outcomes. The Problem-Based Learning model was chosen because it requires students to be active in research and problem-solving processes during learning. This study aims to increase the motivation to learn among class XI IPA 2 students at SMAN 2 Denpasar for the 2023/2024 academic year. The research subjects were 45 students from class XI IPA 2. The study used two cycles with four stages in each cycle: planning, implementation, observation, and reflection. Data collection was done by distributing questionnaires related to student motivation. The obtained data was then analyzed qualitatively. The pre-cycle motivation to learn among students was 44.02, while the first cycle questionnaire results showed an achieved result with an average of 62.84. Subsequently, the second cycle questionnaire results showed an achieved result with an average of 81.20. Based on the research results, it was found that the implementation of the Problem-Based Learning model in mathematics learning for class XI IPA 2 students at SMA Negeri 2 Denpasar in the 2023/2024 academic year can increase student motivation.